2015
DOI: 10.1142/s021833901550031x
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Intra-Venous Glucose Tolerance Test Model With Two Discrete Delays

Abstract: A mathematical model for Intra-Venous Glucose Tolerance Test (IVGTT) with explicit glucose–insulin interaction is presented as a system of delay differential equation with discrete time delays and its important mathematical features are analyzed. This model includes the positivity and boundedness of the solution. An unique equilibrium point is found and its local stability is investigated. Using the Lyapunov functional approach, we show the global stability of the unique equilibrium point. The length of delay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Pitchaimani et.al [38] considered a two discrete delay for IVGTT model, they showed that in theory, the IVGTT model [6] is best fitting for all existing data. But our model shows that, it satisfies not only the existing data also the 40 subjects (for the minimum range R 1 and the maximum range R 2 , the parameters estimate from the WLS model) [35] ISSN: 2456-8686, Volume 1, Issue 1, 2017:1-30 DOI : http://doi.org/10.26524/cm1…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pitchaimani et.al [38] considered a two discrete delay for IVGTT model, they showed that in theory, the IVGTT model [6] is best fitting for all existing data. But our model shows that, it satisfies not only the existing data also the 40 subjects (for the minimum range R 1 and the maximum range R 2 , the parameters estimate from the WLS model) [35] ISSN: 2456-8686, Volume 1, Issue 1, 2017:1-30 DOI : http://doi.org/10.26524/cm1…”
Section: Discussionmentioning
confidence: 99%
“…In [36], we consider for each α > 0, the bnanach space of fading memory type, Proposition 2.1 As in [38], the time derivatives of the postibe solutions (5) are bounded.…”
Section: Well-posedness Of the Model And Feasibility Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial conditions for system (2) are chosen at t = 0 as Theorem 2.1 All solutions of system (2) are positive and bounded in C + , for all t > 0. Furthermore, all solutions eventually enter and remain in the following bounded region:…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Many works have been developed for various infectious diseases using different types of delay differential equation models [1,2,3,4,5,6,7,13,14]. Simple models are useful for verifying the various hypotheses and for determining the method of medical treatments.…”
Section: Introductionmentioning
confidence: 99%